O'Connor's argument for indeterminism. (1st September 2016) - Murray, Samuel
Abstract : Timothy O'Connor has recently defended a version of libertarianism that has significant advantages over similar accounts. One of these is an argument that secures indeterminism on the basis of an argument that shows how causal determinism threatens agency in virtue of the nature of the causal relation involved in free acts. In this paper, I argue that while it does turn out that free acts are not causally determined on O'Connor's view, this fact is merely stipulative and the argument that he presents for this conclusion begs the question.